Peranan Kaum Tarekat dalam Melawan Penjajah - Muzaiyana Muzaiyana (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2017)
Islamic community in Java, rich in heritage that is the legacy of their ancestors, including the legacy of literary works and history. These works, in substance reflects the community's culture, which has a soul that is very unique time and unique. Recognized that Islam in Java grow and develop naturallythrough interaction with local culture. This process continued until the end of Islam that developed in Java known as the Islamic Javanese beliefs, Islam has experienced aculturatif and syncretic. Javanese Islamic model can be traced through the works that have left a legacy, one of whom is the workRanggawarsita, Serat Wirid Hidayat Jati.